ELICITING MATHEMATICAL THINKING OF STUDENTS IN ADDITION OF FRACTIONS THROUGH REALISTIC MATHEMATICS EDUCATION - Anwar, Lathiful (Universitas Ahmad Dahlan, 2011)
This paper focuses on a Grade 4 mathematics intervention that has been developed and implemented in grade four of primary school in Surabaya, Indonesia. The theory of Realistic Mathematics Education (RME) has been applied in a sequence of instructional activities, which aims to assist low attaining learners in supporting students thinking in the addition of fractions. Based on the premise that eliciting and addressing learners alternative conceptions in mathematics is beneficial in assisting them to improve their understanding, the paper seeks to explore the role that RME plays pertaining to this particular supposition. The paper presents and discusses examples of learners responses to contextual problems given to them during the course of the instructional activities.